A hierarchical access control scheme based on Lagrange interpolation for mobile agents. (July 2018) - Hsiao, Tsung-Chih; Wu, Zhen-Yu; Chen, Tzer-Long; Chung, Yu-Fang; Chen, Tzer-Shyong
The mobile agent is functioning as an information exchanger with hosts. In order to reduce the communication time that the host sent to the members of a large system. This article proposes to use a function defined by Lagrange polynomial to compute decryption key. Each host will be given a decryption key to access the confidential document by inputting a secret key into an interpolation function which is generated from Lagrange interpolation. Since tasks are done by the mobile agent, the whole process will be performed within a short time period because there is no physical connection between the end devices. The information exchange occurs at the end hosts.